Penguatan Branding dan Digitalisasi Marketing UMKM Marning Desa Pontang, Kecamatan Ambulu, Kabupaten Jember - Mainatul Ilmi; Yani Dahliani; Wiwik Fitria Ningsih; Aditya Fajri Ilhamsyah; Evi Ludya Agustin; Agus Prasetyo; Nur Habibina; Putri Nur Indah Sari; Alni Nurafia (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
Village SDGs can be achieved with the synergy of various parties starting from government, academics and society. Through the Community Service Program implemented by academics including lecturers and students who are actively involved in community business development programs, it can help improve community welfare. This program is partnering with MSMEs Marning which is owned by Mr. Misladi in Pontang Village, Ambulu District, Jember. The partner problems are related to the lack of identity on the product, still using standard plastic packaging, and not being familiar with digital marketing. The solution provided to overcome this problem is to provide assistance in strengthening branding by creating product logos, updating packaging shapes, installing banners and registering businesses on Google Map. Assistance is also provided by providing insight into digital marketing to expand marketing.